Real time multi face detection - Sabado, Faith (2014)
Face detection has become the center of attraction over the years among the researchers in the computer vision field. Not only because it provides as initial platform for face recognition but it is also used in many applications such as video surveillance, responsive user interface, intelligent focus and in the recent years, in social networking sites such as Facebook.